Annual report on status of cancer in China, 2010 - Chen, Wanqing; Zheng, Rongshou; Zhang, Siwei; Zhao, Ping; Zeng, Hongmei; Zou, Xiaonong; He, Jie (Chinese Journal of Cancer Research; Vol 26, No 1 (February 27, 2014): Chinese Journal of Cancer Research, 2014)
Objective: Population-based cancer registration data in 2010 were collected, evaluated and analyzed by the National Central Cancer Registry (NCCR). Cancer incident new cases and cancer deaths were estimated. Methods: There were 219 cancer registries submitted cancer incidence and death data in 2010. All data were checked and evaluated on basis of the criteria of data quality from NCCR. Total 145 registries’ data were qualified and accepted for cancer statistics in 2010. Pooled data were stratified by urban/rural, area, sex, age group and cancer site. Cancer incident cases and deaths were estimated using age-specific rates and national population. The top ten common cancers in different groups, proportion and cumulative rate were also calculated. Chinese population census in 2000 and Segi’s population were used for age-standardized incidence/mortality rates. Results: All 145 cancer registries (63 in urban and 82 in rural) covered a total of 158,403,248 population (92,433,739 in urban and 65,969,509 in rural areas). The estimates of new cancer incident cases and cancer deaths were 3,093,039 and 1,956,622 in 2010, respectively. The morphology verified cases (MV%) accounted for 67.11% and 2.99% of incident cases were identified through death certifications only (DCO%) with mortality to incidence ratio (M/I) of 0.61. The crude incidence rate was 235.23/100,000 (268.65/100,000 in males, 200.21/100,000 in females), age-standardized incidence rates by Chinese standard population (ASIRC, 2000) and by world standard population (ASIRW) were 184.58/100,000 and 181.49/100,000 with the cumulative incidence rate (0-74 years old) of 21.11%. The cancer incidence and ASIRC were 256.41/100,000 and 187.53/100,000 in urban areas whereas in rural areas, they were 213.71/100,000 and 181.10/100,000, respectively. The crude cancer mortality in China was 148.81/100,000 (186.37/100,000 in males and 109.42/100,000 in females), age-standardized incidence rates by Chinese standard population (ASMRC, 2000) and by world standard population (ASMRW) were 113.92/100,000 and 112.86/100,000, and the cumulative incidence rate (0-74 years old) was 12.78%. The cancer mortality and ASMRC were 156.14/100,000 and 109.21/100,000 in urban areas, whereas in rural areas, they were 141.35/100,000 and 119.00/100,000 respectively. Lung cancer, gastric cancer, colorectal cancer, liver cancer, esophageal cancer, pancreas cancer, encephaloma, lymphoma, female breast cancer and cervical cancer, were the most common cancers, accounting for 75% of all cancer cases in urban and rural areas. Lung cancer, gastric cancer, liver cancer, esophageal cancer, colorectal cancer, pancreatic cancer, breast cancer, encephaloma, leukemia and lymphoma accounted for 80% of all cancer deaths. Conclusions: The coverage of cancer registration population had a rapid increase and could reflect cancer burden in each area and population. As the basis of cancer control program, cancer registry plays an irreplaceable role in cancer epidemic surveillance, evaluation of cancer control programs and making anti-cancer strategy. China is facing serious cancer burden and prevention and control should be enhanced.